2015
DOI: 10.1007/s11356-015-4193-4
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.)

Abstract: Little information is available on the role of glycinebetaine (GB) in chromium (Cr) tolerance while Cr toxicity is widespread problem in crops grown on Cr-contaminated soils. In this study, we investigated the influence of GB on Cr tolerance in wheat (Triticum aestivum L.) grown in sand and soil mediums. Three concentrations of chromium (0, 0.25, and 0.5 mM) were tested with and without foliar application of GB (0.1 M). Chromium alone led to a significant growth inhibition and content of chlorophyll a, b, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 54 publications
(69 reference statements)
11
86
0
Order By: Relevance
“…Meanwhile, the excessive oxalic and tartaric acids in roots under Cd stress may contribute to a lower translocation factor with 20 mM GB application plants to non-GB treatment. Furthermore, GB played an important role in effective protection against lead and chromium (Ali et al 2015;Bhatti et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the excessive oxalic and tartaric acids in roots under Cd stress may contribute to a lower translocation factor with 20 mM GB application plants to non-GB treatment. Furthermore, GB played an important role in effective protection against lead and chromium (Ali et al 2015;Bhatti et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress may occur in plants when they are exposed to various environmental stresses, both biotic and abiotic, including heavy metal stress (Adrees et Ali et al, 2015aAli et al, , 2015bHabiba et al, 2015;Noman et al, 2015). However, Si application may reduce oxidative stress in plants by reducing the production of reactive oxygen species (ROS) and by enhancing the activities of antioxidant enzymes.…”
Section: Enhancement In Antioxidant Defense Systemmentioning
confidence: 99%
“…It has been widely reported that accumulation of heavy metals in plants may cause many biochemical, structural and physiological changes (Nagajyoti et al, 2010;Afshan et al, 2015). Heavy metals negatively affected plant growth, biomass and photosynthesis (Wuana and Okieimen, 2011;Adrees et al, 2015;Ali et al, 2015aAli et al, , 2015b. In an excess, heavy metals also affect the accumulation and translocation of essential elements by plants (Wagner, 1993;Wuana and Okieimen, 2011;Zia-ur-Rehman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different actions have been taken to reduce heavy metal uptake and toxicity in plants including exogenous application of different materials such as humic substances Noman et al 2015), osmoprotectants (Adrees et al 2015c;Ali et al 2015b), soil amendments (Rehman et al 2015) and silicon (Rizwan et al 2012;Adrees et al 2015b;Keller et al 2015). Silicon (Si) is the second most abundant element of the earth's crust and is considered a quasi-essential element for plant growth and development (Epstein and Bloom 2005).…”
Section: Downloaded By [University Of Otago] At 22:57 24 July 2015mentioning
confidence: 99%